Monocyte chemoattractant protein-1 in patients with different types of diabetes mellitus: clinical and practical significance - Ivan I. Golodnikov; Margarita D. Samsonova; Irina V. Kononenko; Tatiana V. Nikonova; Elizaveta S. Podshivalova; Ekaterina K. Markelova; Ekaterina V. Bondarenko; Marina Yu. Loginova; Marina V. Shestakova (Consilium Medicum, 2025)
Background. Monocyte chemoattractant protein-1 (MCP-1) plays a crucial role in inflammatory processes by recruiting monocytes and macrophages to sites of inflammation. Inflammation is closely linked to poor control of diabetes mellitus (DM), characterized by significant glycemic fluctuations and prolonged hyperglycemia, as well as subclinical, low-grade inflammation of adipose tissue in type 2 DM. Elevated levels of MCP-1 have been associated with both type 1 and type 2 DM; however, data on its role in the pathogenesis of latent autoimmune diabetes in adults (LADA) are extremely limited.